2022
DOI: 10.3390/app12094751
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of an Immature Permanent Tooth with Periapical Periodontitis Using Concentrated Growth Factor Assisted by Erbium Laser (2940 nm) Irrigation: A Case Report

Abstract: Revascularization has been incorporated into endodontic practice and become a viable treatment alternative for immature teeth with pulp necrosis. Thorough disinfection of the root canal is a key factor for successful revascularization. An erbium: yttrium–aluminium–garnet (Er: YAG) laser has been proved advantageous for efficient root canal disinfection. This article reports one case of periapical periodontitis caused by a fractured occlusal tubercle. Revascularization assisted by Er: YAG laser irrigation was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Good coronal seal restorations are essential for successful treatment in REPs [8]. We found that teeth sealed with CR (95.7%) had a higher success rate than those sealed with GIC (86.3%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Good coronal seal restorations are essential for successful treatment in REPs [8]. We found that teeth sealed with CR (95.7%) had a higher success rate than those sealed with GIC (86.3%).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, CGF is superior to PRP and PRF in terms of preparation and composition as an ideal biomaterial [6]. Given its characteristics of autogenesis, clinical applicability and biodegradability, CGF has gained popularity in periodontal regeneration, facial reconstruction and dental implants fields for repairing bone defects and promoting soft-tissue healing [6,8]. More recently, the application of CGF has been investigated as a possible scaffold for endodontic regeneration and has shown promising clinical and radiographic results [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 These pairs of consecutive laser pulses produce shock waves and enhance fluid flow and photoacoustic currents, which eventually contribute to optimal root canal cleansing and disinfection. 31,32 Yu et al 35 described a case with periapical periodontitis treated with revascularization assisted with Er:YAG laser irrigation. Following the removal of necrotic pulp, the canal was rinsed with 0.5% sodium hypochlorite (NaOCl) solution.…”
Section: Laser-activated Irrigationmentioning
confidence: 99%